Meningkatkan Hasil Belajar Pendidikan Agama Islam dengan Instrumen Permainan Bendera di Kelas I SD Negeri 09 Kepahiang - Fajaria, Fajaria (UNIB Press, 2020)
the Islamic religion itself, ranging from the Al-Qur'an, recognize the aspects of the pillars of Islam, faith in Alah, to the Qadha and Qadar. Be lauded in everyday life and avoid reprehensible behavior. Get to know and implement the pillars of Islam that starts from the recitation of the shahada to find out the procedures for performing the Hajj. Tell the stories of the prophets and take an example from these stories and tell the story of despicable people in everyday life. All of that will be the provision of the students later. But all aspects will be difficult for students to digest if conveyed in a less conventional way. For this reason, a research is needed. This Classroom Action Research (CAR) has the intent and purpose of improving Islamic Education learning outcomes through the instrument of flag Permainan. This research was conducted in two cycles. The participants in this study were grade 1, students at SD Negeri 09 Kepahiang. The number of students is 29 children. The data collection method uses teacher activity observation sheets, student activities and tests to get data on learning outcomes. The results and data obtained from Cycle I and Cycle II emphasize that by using the Flag Game instrument, a significant increase in learning outcomes was found with good scores and very good grades, from initially only 48.1% to 92.8%.